Pengaruh Perkembangan Karir dan Komunikasi Terhadap Produktivitas Pegawai pada Dinas Pendidikan Pemuda dan Olahraga Kabupaten Bima - Muktadir Muktadir; Muhammad Yusuf; Sugeng Widakdo (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine whether career development and communication have a significant effect on employee productivity at the Department of Education, Youth, and Sports of Bima Regency. The research instrument used was a questionnaire based on a Likert scale. The population of this study consisted of 152 employees at the Department of Education, Youth, and Sports of Bima Regency, including 60 Civil Servants (PNS), 27 Government Employees with Work Agreements (PPPK), and 65 Regional Honorary Employees. The sample comprised 87 State Civil Apparatus (ASN) employees, consisting of 60 Civil Servants and 27 Government Employees with Work Agreements, selected using a purposive sampling technique. Data were collected through observation, questionnaires, and a literature review. The data were analyzed using validity and reliability tests, multiple linear regression analysis, classical assumption tests, correlation coefficient analysis, coefficient of determination analysis, t-tests, and F-tests with the assistance of SPSS version 26 for Windows. The results indicate that career development has a significant effect on employee productivity, communication has a significant effect on employee productivity, and career development and communication simultaneously have a significant effect on employee productivity at the Department of Education, Youth, and Sports of Bima Regency.